Justice, wellbeing and social capital - Tim Hughes (New Zealand Government, The Treasury, 2020)
Wellbeing and social capital are central concepts in the policy discourse of the new government. At the same time, inspired in part by the Capabilities Approach of Sen and Nussbaum, Treasury has been developing its living standards framework. This discussion paper makes a first attempt at exploring these concepts from the perspective of the justice system. The aim is to support an ongoing conversation within the justice system, and between the justice system and wider stakeholders.
Keywords: 330; Zufriedenheit; Sozialkapital; Capability-Ansatz; Gerechtigkeit; Lebensstandard; Rechtsordnung; Neuseeland